Growing microgreens in greenhouses - Kovaliova, V. K. (ТДАТУ, 2021)
If you are ready to try your luck with growing microgreens, you may be able to cut back on your grocery store cost and make a side profit on selling the excess microgreens you grow. If you’ve already started on your farming journey and have a greenhouse, you can jump straight to buying your seeds and growing your crops.
Keywords: microgreens; Self-cultivation of microgreens; healthy fresh food